KECERDASAN FINANSIAL DALAM PERILAKU KEUANGAN DALAM PERSPEKTIF AL-QURAN - Nur Arfiyah Febriani; Devy Susanty (Universitas PTIQ Jakarta, 2023)
The conclusion of this article is that financial intelligence through financial behavior from an al-Quran perspective is intelligence as a combination of financial, spiritual, and social intelligence which is implemented through responsible financial behavior for managing assets, starting from how to acquire assets, manage and distribute them. This financial intelligence will provide benefits for oneself (shalihûn lî an-nafs), family (shalihûn lî al-usrah), the environment (shalihûn lî al-bî'ah) and the benefit of humanity (mashlahâtun li an-nâs) which will lead to Man's devotion to Allah Swt and everything he does is aimed solely at carrying out his noble duties as caliph (prospered of the earth) and servant of Allah Swt, which is reflected in balanced financial behavior between worldly needs and investments in the hereafter